PIPN IMPROVES THE APPLICATION OF SCIENCE AND TECHNOLOGY AS WELL AS STAGE MAKEUP, MAHENDI, DIGITAL MARKETING AND VIDEO CONTENT CREATOR SKILLS FOR PKK MOTHERS AND FEMALE TEENS IN BALAI KALIKI TRADITIONAL VILLAGE, PAYAKUMBUH CITY - Vivi Efrianova; Murni Astuti; Mitra Lusiana; Vici Syahril Chairani; Reflianto, Reflianto (Journal of Community Service, 2025)
The Program Integrasi Prodi dan Nagari (PIPN) implemented in Kampung Adat Balai Kaliki, Payakumbuh City, aims to enhance the application of science and technology as well as improve community skills particularly among PKK women and young women in stage makeup, mahendi art, digital marketing, and video content creation. This initiative was motivated by the village’s potential as a cultural tourism destination that regularly hosts artistic and traditional events, yet faces limitations in local human resource skills. The program employed lectures, demonstrations, hands-on practice, and mentoring methods to deliver its training activities. Results indicate significant improvement in participants’ technical competencies in stage makeup and Minangkabau-inspired mahendi, as well as in digital marketing and creative video production. Beyond individual capacity building, the program fostered women’s empowerment, increased family income, and promoted local cultural tourism. Overall, this PIPN initiative exemplifies an effective collaboration between higher education institutions and local communities to strengthen culture-based creative economies.